2010
DOI: 10.1007/s12011-010-8698-x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Liver Injury in Mice Caused by Lanthanoids

Abstract: It has been proven that higher dose of lanthanoid (Ln) can induce liver toxicities, but the mechanisms and the molecular pathogenesis are still unclear. In this study, LaCl₃, CeCl₃, and NdCl₃ at a higher dose of 20 mg/kg body weight was injected into the abdominal cavity of ICR mice for 14 consecutive days, and the inflammatory responses of liver of mice were investigated by histopathological test, real-time quantitative reverse transcription polymerase chain reaction (RT-PCR), and enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…However, whether 4f electronic shell and alterable valence characteristics of Ln exert special toxicity on animals has not been carefully investigated. Recently, our researches showed that exposure to Ln damaged spleen, lung, liver, and brain of mice, which was greatest in Ce 3+ treatment, medium in Nd 3+ treatment, and least in La 3+ treatment [11][12][13][14][15]. However, little is known about the effects of Ln on several organs damages simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether 4f electronic shell and alterable valence characteristics of Ln exert special toxicity on animals has not been carefully investigated. Recently, our researches showed that exposure to Ln damaged spleen, lung, liver, and brain of mice, which was greatest in Ce 3+ treatment, medium in Nd 3+ treatment, and least in La 3+ treatment [11][12][13][14][15]. However, little is known about the effects of Ln on several organs damages simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that abdominal exposure to La 3+ , Ce 3+ , and Nd 3+ at dose of 20 mg/kg BW for 14 days caused oxidative stress in the mouse spleen, liver, brain, and hepatic inflammatory responses. Among the three treatments, the Ce 3+ -treated group exhibited the most severe damage, next in the Nd 3+ -treated group, and the least in the La 3+ -treated group [13][14][15][16]. However, these studies did not refer to the neurotoxicity of cerium under this dosage.…”
mentioning
confidence: 99%
“…Serum GPT, AST, ALP, LDH, and TG are all used for clinical indication of injuries of liver. 26 BUN is an important indicator of renal function. 27 Increased GPT, AST, ALP, LDH, TG, and HIS in MWWE-treated mice indicated that MWWE exposure resulted in dysfunction of liver.…”
Section: ■ Discussionmentioning
confidence: 99%